High blood pressure: prevalence and adherence to guidelines in a population-based cohort (Swiss Medical Weekly, 2016)
QUESTIONS UNDER STUDY: High blood pressure, the single leading health risk factor worldwide, contributes greatly to morbidity and mortality. This study aimed to add to the understanding of diagnosed and undiagnosed high blood pressure in Switzerland and to evaluate adherence to hypertension guidelines. METHODS: Included were 3962 participants from the first (2001–2003) and second (2010–2011) follow-ups of the population-based Swiss Cohort Study on Air Pollution and Lung and Heart Disease in Adults. High blood pressure was defined as blood pressure ≥140/90 mm Hg and the prevalence of doctor-diagnosed hypertension was based on questionnaire information. RESULTS: High blood pressure was found in 34.9% of subjects, 49.1% of whom were unaware of this condition; 30.0% had doctor-diagnosed hypertension and, although 82.1% of these received drug treatments, in only 40.8% was blood pressure controlled (